Formation of DBPs and halogen-specific TOX in the presence of iopamidol and chlorinated oxidants. (July 2018) - Ackerson, Nana Osei B.; Machek, Edward J.; Killinger, Alexis H.; Crafton, Elizabeth A.; Kumkum, Pushpita; Liberatore, Hannah K.; Plewa, Michael J.; Richardson, Susan D.; Ternes, Thomas A.; Duirk, Stephen E.
Abstract: Iopamidol is a known direct precursor to iodinated and chlorinated DBP formation; however, the influence of iopamidol on both iodo/chloro-DBP formation has yet to be fully investigated. This study investigated the effect of iopamidol on the formation and speciation of halogen-specific total organic halogen (TOX), as well as iodo/chloro-DBPs, in the presence of 3 source waters (SWs) from Northeast Ohio and chlorinated oxidants. Chlorination and chloramination of SWs were carried out at pH 6.5–9.0 and, different iopamidol and dissolved organic carbon (DOC) concentrations. Total organic iodine (TOI) loss was approximately equal (22–35%) regardless of SW. Total organic chlorine (TOCl) increased in all SWs and was substantially higher in the higher SUVA254 SWs. Iopamidol was a direct precursor to chloroform (CHCl3 ), trichloroacetic acid (TCAA), and dichloroiodomethane (CHCl2 I) formation. While CHCl3 and TCAA exhibited different formation trends with varying iopamidol concentrations, CHCl2 I increased with increasing iopamidol and DOC concentrations. Low concentrations of iodo-acids were detected without discernible trends. Total trihalomethanes (THMs), total haloacetic acids (HAAs), TOCl, and unknown TOCl (UTOCl) were correlated with fluorescence regional volumes and SUVA254 . The yields of all these species showed a strong positive correlation with fulvic, humic, and combined humic and fulvic regions, as well as SUVA254 . Iopamidol was then compared to the 3 SWs with respect to DBP yield. Although the SUVA254 of iopamidol was relatively high, it did not produce high yields of THMs and HAAs compared to the 3 SWs. However, chlorination of iopamidol did result in high yields of TOCl and UTOCl. Highlights: Iopamidol is a direct and indirect precursor in the formation of chloro/iodo-DBPs. Dichloroiodomethane formation increased as iopamidol concentration increased. Chloroform yields were increased with iopamidol present during chlorination. Trichloroacetic acid yields were unchanged or suppressed with iopamidol present. Iopamidol substantially increased total organic chloride yield during chlorination.